2011
DOI: 10.1007/s10965-011-9749-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel epoxidized natural rubber toughened polyamide 6/halloysite nanotubes nanocomposites

Abstract: A novel ternary epoxidized natural rubber (ENR-50) toughened polyamide 6/halloysite nanotubes (PA6/ HNTs) nanocomposites were successfully prepared by extrusion followed by injection molding. The HNTs revealed a favourable interaction with the PA6 matrix as seen by the improvement in mechanical properties and presence of a new FTIR vibrational peak. The ENR-50 showed an improvement of the impact strength up to 300% with a super tough characteristic at only 15 wt% ENR-50. The naturally occurring nanotubes prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…A similar trend is also observed with HNT C. As an example, the value of Young's modulus for PA11/HC5 increases by 20%, while its impact strength decreases by almost 44% compared to that of neat PA11. All these results are consistent with those reported in the literature [1,18,[46][47][48], which are attributed to the reinforcing effect of the clay filler. The enhancement of the tensile strength of the PA11 nanocomposite samples could be due to the intrinsic stiffness of the individually dispersed halloysite nanotubes [18] and also to some affinity between PA11 and HNTs.…”
Section: Mechanical Propertiessupporting
confidence: 93%
“…A similar trend is also observed with HNT C. As an example, the value of Young's modulus for PA11/HC5 increases by 20%, while its impact strength decreases by almost 44% compared to that of neat PA11. All these results are consistent with those reported in the literature [1,18,[46][47][48], which are attributed to the reinforcing effect of the clay filler. The enhancement of the tensile strength of the PA11 nanocomposite samples could be due to the intrinsic stiffness of the individually dispersed halloysite nanotubes [18] and also to some affinity between PA11 and HNTs.…”
Section: Mechanical Propertiessupporting
confidence: 93%
“…In particular, ENR is still able to generate strain‐induced crystallization up to a 50 mol % epoxidation level . However, compared with its native natural rubber counterpart, ENR exhibits various additional advantages, such as a good oil resistance, low gas permeability, good adhesive ability, and enhanced compatibility . In addition, the epoxy groups of ENR are randomly distributed along the polymer backbone and can readily react with many nucleophilic reagents for further modification or crosslinking .…”
Section: Introductionmentioning
confidence: 99%
“…1 However, compared with its native natural rubber counterpart, ENR exhibits various additional advantages, such as a good oil resistance, 2 low gas permeability, 3 good adhesive ability, and enhanced compatibility. 4,5 In addition, the epoxy groups of ENR are randomly distributed along the polymer backbone and can readily react with many nucleophilic reagents for further modification or crosslinking. [6][7][8][9] Previous studies have shown that ENR can be crosslinked by difunctional or multifunctional amines or acids via the ring opening of the epoxy groups in the presence of catalysts (phenol or bisphenol A for amines and imidazole for acids).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of a hard rigid filler considerably decreased the impact strength as the filler that was dispersed in the polymer matrix acted as stress concentrator. Sharif et al . reported that the impact strength of the PA6/halloysite nanotube (HNT) nanocomposites blend increased up to 300% with the addition of 20 wt % ENR‐50 as compared to that of the PA6/HNT nanocomposites alone.…”
Section: Enr As An Impact Modifier In Thermoplasticsmentioning
confidence: 99%